2010
DOI: 10.1089/dia.2009.0159
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-IV Inhibitors Are Efficient Adjunct Therapy in HNF1A Maturity-Onset Diabetes of the Young Patients—Report of Two Cases

Abstract: DPP-IV inhibitors may be an effective tool of combined therapy in HNF1A MODY, and they seem to improve beta-cell function under fasting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
1
19
0
2
Order By: Relevance
“…The findings in our trial are, however, consistent with recent case studies reporting beneficial effects of dipeptidyl peptidase-4 inhibitors in patients with HNF1A diabetes when combined with other oral glucose-lowering drugs (14,15) or with liraglutide as adjunct therapy to SU and basal insulin (16). Whether monotherapy with GLP-1RA is sufficiently effective to maintain an acceptable long-term glycemic regulation in patients with HNF1A diabetes is not clear from our trial.…”
Section: 028supporting
confidence: 79%
See 1 more Smart Citation
“…The findings in our trial are, however, consistent with recent case studies reporting beneficial effects of dipeptidyl peptidase-4 inhibitors in patients with HNF1A diabetes when combined with other oral glucose-lowering drugs (14,15) or with liraglutide as adjunct therapy to SU and basal insulin (16). Whether monotherapy with GLP-1RA is sufficiently effective to maintain an acceptable long-term glycemic regulation in patients with HNF1A diabetes is not clear from our trial.…”
Section: 028supporting
confidence: 79%
“…In 2006, Tuomi et al (11) demonstrated that during physical exercise in patients with HNF1A diabetes (light cycling for 30 min approximately 2 h after ingesting a meal), hypoglycemia was observed in 40% of subjects treated with an SU (glibenclamide); one patient experienced hypoglycemia for 12 h. In contrast to the glucose-independent insulinotropic effect of SUs, GLP-1 receptor agonists (GLP-1RAs) exert an insulinotropic effect in a strictly glucose-dependent manner, with no effect at PG concentrations ,4-5 mmol/L (12,13), translating into a low risk of hypoglycemia. Therefore, GLP-1RA treatment might be safe and efficacious for patients with HNF1A diabetes, but so far only a few cases have been reported (14)(15)(16).…”
mentioning
confidence: 99%
“…Treatment of patients with MODY using an incretinbased strategy has been described in a few cases (23,24). Our study demonstrates that HNF1A-diabetes shares incretin-related pathophysiology with type 2 diabetes, i.e., reduced incretin effect, which was one of the incentives for incretin-based treatment for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 60%
“…Additional data have shown that patients with MODY 3 are more responsive to sulfonylureas than metformin (16 ). Several case reports have suggested that dipeptidyl peptidase-IV inhibitors may further improve blood glucose control when used in combination with sulfonylureas in MODY 3 patients (17,18 ). More studies will be required to confirm these observations and determine whether incretin analogs have similar effects.…”
Section: Monogenic Diabetes Subtypesmentioning
confidence: 99%